2003
DOI: 10.1128/aac.47.8.2445-2449.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effective Immunomodulatory Treatment ofEscherichia coliExperimental Sepsis with Thalidomide

Abstract: Thalidomide, an agent which inhibits biosynthesis of tumor necrosis factor alpha (TNF-␣) and which is used to treat a variety of chronic inflammatory conditions, was investigated as therapy for experimental sepsis. Sepsis was induced by intraperitoneal injection of 10 7 CFU of Escherichia coli per kg of body weight to 80 Wistar rats divided into four groups. Group A consisted of 24 control animals that did not receive any pretreatment, group B consisted of 18 vehicle-treated control animals pretreated with see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
0
16
0
3
Order By: Relevance
“…Pretreatment with potent immunomodulatory agents in animal studies may have led to the failure of previous clinical trials (1). Administration of clarithromycin in parallel with bacterial challenge allows (i) avoidance of pretreatment; (ii) the ability to achieve the desired drug levels within 30 to 60 min after intravenous infusion, i.e., later than bacterial inoculation; and (iii) documentation of whether the secretion of proinflammatory mediators is prevented, which constitutes the necessary step before proceeding to drug administration in the event of the presence of clinical symptoms of sepsis (9).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pretreatment with potent immunomodulatory agents in animal studies may have led to the failure of previous clinical trials (1). Administration of clarithromycin in parallel with bacterial challenge allows (i) avoidance of pretreatment; (ii) the ability to achieve the desired drug levels within 30 to 60 min after intravenous infusion, i.e., later than bacterial inoculation; and (iii) documentation of whether the secretion of proinflammatory mediators is prevented, which constitutes the necessary step before proceeding to drug administration in the event of the presence of clinical symptoms of sepsis (9).…”
Section: Animalsmentioning
confidence: 99%
“…A total of 10 8 CFU of the P. aeruginosa isolate per kg in a volume of 0.1 ml was injected into the renal pelvis, proximal to the suture, with a 26-gauge needle. The bacterial inoculum was selected on the basis of those used in previous studies (9). The peritoneal cavity and the abdominal wall were then closed in layers.…”
Section: Animalsmentioning
confidence: 99%
“…As such, inhibition of TNF-␣ has provided prolonged survival in a variety of animal models of sepsis induced after challenge with LPS or Gram-negative bacteria such as E. coli (Tracey et al, 1987;Giamarellos-Bourboulis et al, 2003). The biological significance of TNF-␣ as the acute proinflammatory cytokine leading to early death has been shown in experiments using TNF-deficient mice.…”
mentioning
confidence: 99%
“…[17][18][19][20][21] There are interesting reports suggesting that thalidomide improves endotoxin-or alcohol-induced liver injury, 22,23) and prolongs the survival rate following the experimental sepsis induced by endotoxin or bacterial challenge in rats. 24,25) Shimazawa et al 26) have reported that thalidomide and its analogs have NO synthase (NOS)-inhibitory activity in vitro, but the activity of thalidomide is weak. Enomoto et al 27) reported that thalidomide abolishes the endotoxin-induced increase in CD14 expression in Kupffer cells in vitro.…”
mentioning
confidence: 99%
“…The dose of thalidomide used in this study was chosen on the basis of that used in previous studies. 25) Twenty-four hours after injection of endotoxin or saline, antipyrine clearance experiments were conducted, since we previously reported that the level of endotoxin-induced decrease in hepatic drug-metabolizing enzyme activity reaches the maximum 24 h after endotoxin administration. 29) Rats received a bolus intravenous injection of antipyrine (20 mg/kg of body weight), which was dissolved in saline at the concentration of 10 mg/ml.…”
mentioning
confidence: 99%